65.2k views
0 votes
Solve x 3+3(x+2)=-24​

User MegaHit
by
5.4k points

2 Answers

1 vote

Answer:

x=-11

Explanation:

3+3x=6=-24

3x+9=-24

3x=-33

x=-11

User Hannson
by
5.7k points
3 votes

Answer:

x = -11

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

Explanation:

Step 1: Define Equation

3 + 3(x + 2) = -24

Step 2: Solve for x

  1. Distribute 3: 3 + 3x + 6 = -24
  2. Combine like terms: 3x + 9 = -24
  3. Isolate x term: 3x = -33
  4. Isolate x: x = -11

Step 3: Check

Plug in x into the original equation to verify it's a solution.

  1. Substitute in x: 3 + 3(-11 + 2) = -24
  2. Add: 3 + 3(-9) = -24
  3. Multiply: 3 - 27 = -24
  4. Subtract: -24 = -24

Here we see that -24 does indeed equal -24.

∴ x = -11 is the solution to the equation.

User Iyasar
by
4.8k points